Assessment Dynamics the Development of Financial Markets in the UK and Japan in the Context of COVID-19 Pandemic - Lyashenko, V.; Bitner, I.; Bilotserkivskyi, O. (IJAMR, 2022)
The negative dynamics of the spread of the COVID-19 pandemic affects all areas of daily and economic activity. At the same time, the degree of such influence is largely determined by the continuity of the movement of various financial flows, the possibility of their rapid renewal in cases of emergency slowdown or interruption of movement. For the analysis of the movement of financial flows, it is important to study the development of financial markets. It is important to carry out such an analysis from the point of view of different segments of the financial market. At the same time, it is also necessary to take into account the general trend in the development of the financial market, the relationship of its individual segments. This can be done based on the analysis of the relevant stock indexes. The paper considers the dynamics of the real values of stock indices, which reflect the dynamics of the development of individual sectors of the financial market. The paper also takes into account the aspects of conducting a comparative analysis, which allows us to identify common patterns. To do this, we consider the values of the UK and Japan stock indices. To conduct a comparative analysis, we use the methodology for constructing wavelet coherence estimates. The paper presents many graphs and charts for specific real data. This allows you to understand the logic of the study and the results obtained.
Keywords: financial market; wavelet analysis